"Whitewashing and extortion: why human rights-abusing states participate in UN peacekeeping operations". Issue 5 (2nd September 2020) - Levin, Andrew
ABSTRACT: This paper examines the participation of human rights-abusing countries in UN peacekeeping operations. This seemingly growing occurrence raises questions given the UN's emphasis in recent decades on protecting the physical integrity of civilians. How extensive are the contributions of human rights-violators in UN peacekeeping operations? And, what explains this phenomenon? I posit that peacekeeping provision serves two important functions for human rights abusers. First, committing large numbers of peacekeeping personnel helps states to whitewash poor domestic human rights records. Second, by contributing to the provision of an underprovided public good, human rights abusers can extort the international community to prevent interference in their domestic activities. Analysis of data from 1991–2011 shows that human rights abusers make substantially greater contributions to peacekeeping operations, even when holding constant variables such as regime type and wealth. These findings have significant implications for the protection of human rights, both in states that host and contribute peacekeepers.